Molybdenum(VI) dioxo complexes for the epoxidation of allylic alcohols and olefins - Pandhare, Swati L.; Jadhao, Rajesh R.; Puranik, Vedavati G.; Joshi, Pranaya V.; Capet, Frederic; Dongare, Mohan K.; Shubhangi B. Umbarkar; Michon, Christophe; Agbossou-Niedercorn, Francine (Journal of Organometallic Chemistry, 2014)
Several molybdenum(VI) dioxo complexes have been investigated as catalyst precursors for allylic alcohol epoxidation using mainly hydrogen peroxide as oxidant. All catalysts proved to be efficient and selective for the epoxidation of allylic alcohols provided the olefins were rather electron rich. Indeed, electron poor substrates could be converted selectively into the corresponding unsaturated aldehydes. A chiral dioxomolybdenum complex based on an optically pure tridentate Schiff base ligand was synthesized and characterized. Though that complex provided an efficient epoxidation catalyst for allylic alcohols and olefins, no chiral induction was observed. During the X-ray diffraction analysis, the cooling at 100 K led to the appearance of super-lattice reflections on diffraction patterns reflecting an ordering of the structure. Instead of one organometallic species observed at 298 K, three similar complexes of the same molecular structure could be observed in the asymmetric unit at 100 K. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Allylic alcohol; epoxidation; Molybdenum; Oxidation; Peroxide

Monitoring cellular uptake and cytotoxicity of copper(II) complex using a fluorescent anthracene thiosemicarbazone ligand - Kate, Anup N.; Kumbhar, Anupa A.; Khan, Ayesha A.; Joshi, Pranaya V.; Puranik, Vedavati G. (Bioconjugate Chemistry, 2014)
The thiosemicarbazone derivative of anthracene (ATSC, anthracene thiosemicarbazone I) and its copper(II) complex (CuATSC, 2) were synthesized and characterized by spectroscopic, electrochemical, and crystallographic techniques. Interaction of 1 and 2 with calf thymus (CT) DNA was explored using absorption and emission spectral methods, and viscosity measurements reveal a partial-intercalation binding mode. Their protein binding ability was monitored by the quenching of tryptophan emission using bovine serum albumin (BSA) as a model protein. Furthermore, their cellular uptake, in vitro cytotoxicity testing on the HeLa cell line, and flow cytometric analysis were carried out to ascertain the mode of cell death. Cell cycle analysis indicated that 1 and 2 cause cell cycle arrest in sub-G1 phase.